Tratamento de dados FAIR no Projeto Laguna - Luís Ribeiro, Washington; Luiz Pinto, Adilson; Lorensi do Canto, Fabio; da Silva Neubert, Patricia (BiblioCanto, 2023)
Pôster apresentado na 14ª Conferência Lusófona de Acesso Aberto (ConfOA).